Paciente neonatal con síndrome de distrés respiratorio. - Mayorga Vera, Damaris Belén (2020)
A 35-week-old neonatal patient, with acute respiratory distress syndrome, with two hours of life enters emergency with symptoms of shortness of breathing difficulty, during his stay in emergency received oxygenation therapy through non-invasive mechanical ventilation, and antibiotic treatment. The respiratory therapy care process with APGAR scale assessments, Silverman's test, and timely treatment contribute to a good process in the maturation of the child's vital functions and stabilize their breathing allowing the newborn to evolve satisfactorily, for which he was discharged. Acute respiratory distress syndrome, occurs in preterm newborns and is the main cause of morbidity of respiratory origin, encompasses various lung entities, respiratory management in the first hours of life depends not only on which neonate survives but also its prevention in the gestational period and identify the factors that determine the incidence of acute respiratory distress syndrome. The study shows that the management of respiratory therapy care in acute respiratory distress syndrome with correct monitoring allows to evolve favorably to the neonate, avoiding morbidity rates.